Investigation into the Mechanisms of Paeoniae Radix Rubra in the Treatment of Venous Thrombosis Using Network Pharmacology, Bioinformatics, and Molecular Docking Techniques - Xu, Shuo; Hou, Ajiao; Zhang, Jiaxu; Xue, Jinhao; Gao, Shiwen; Jiang, Hai; Yang, Liu (Current Pharmaceutical Design, 2025)
Objective This study investigates the potential targets and mechanisms of Paeoniae Radix Rubra (PRR) in treating Venous Thrombosis (VTE) by employing network pharmacology, bioinformatics analysis, and molecular docking validation. Methods Active components of PRR were identified via TCMSP. VTE-related genes were screened from GEO datasets, and WGCNA analyzed key modules. A Protein-Protein Interaction (PPI) network was constructed using Cytoscape, followed by immune infiltration analysis. Core targets were functionally annotated via GO and KEGG pathways. Molecular docking and molecular dynamics simulations validated interactions between PRR components and core targets. Results A total of 30 active components of PRR and 21 potential targets for the treatment of VTE were identified. From the PPI network, 10 hub genes were screened. KEGG pathway enrichment analysis demonstrated that the target genes were significantly enriched in pathways, such as the cGMP-PKG signaling pathway, B cell receptor signaling pathway, Th1 and Th2 cell differentiation, and IL-17 signaling pathway. Molecular docking results revealed that MAPK1, NFATC1, and SELP all had good affinity with the screened active components. Among them, MAPK1 and beta-sitosterol exhibited the highest binding energy of -8.73 kcal/mol. Molecular dynamics simulation results from RMSD, RMSF, HBond, and SASA analyses indicated that the beta-sitosterol-MAPK1 complex maintained good stability. Conclusion Through this study, it was found that PRR may act on targets, such as MAPK1 and NFATC1, through components like beta-sitosterol and Stigmasterol. Among them, the complex (beta-sitosterol - MAPK1) may be the key active component that plays a role in treating VTE.
Keywords: Paeoniae Radix Rubra (PRR)